Protein Kinase Signaling Pathways in Plant-Colletotrichum Interaction - Jiang, Lingyan; Zhang, Shizi; Su, Jianbin; Peck, Scott C.; Luo, Lijuan (Frontiers in Plant Science, 2022)
Anthracnose is a fungal disease caused by members of Colletotrichum that affect a wide range of crop plants. Strategies to improve crop resistance are needed to reduce the yield losses; and one strategy is to manipulate protein kinases that catalyze reversible phosphorylation of proteins regulating both plant immune responses and fungal pathogenesis. Hence, in this review, we present a summary of the current knowledge of protein kinase signaling pathways in plant-Colletotrichum interaction as well as the relation to a more general understanding of protein kinases that contribute to plant immunity and pathogen virulence. We highlight the potential of combining genomic resources and phosphoproteomics research to unravel the key molecular components of plant-Colletotrichum interactions. Understanding the molecular interactions between plants and Colletotrichum would not only facilitate molecular breeding of resistant cultivars but also help the development of novel strategies for controlling the anthracnose disease.